Targeting DHFR in breast cancer: exploring expression patterns and identifying potential inhibitors through docking studies - Araf, Faiaz Fahim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.